Atividade antifúngica da palmatina frente a isolados de Candida spp. resistentes a azólicos e sua atividade contra biofilme formado e em formação - Campos, Rosana de Sousa (2017)
Currently, the incidence of fungal infections has been increasing and in a prominent position, those caused by species of the genus Candida, which is the most isolated microorganism in hospital sepsis. The most frequently isolated species was Candida albicans, but this scenario has been changing with the increase of non-albicans species, which are more resistant to fluconazole. Due to the resistance problem and the fact that there are few antifungal drugs available on the market, it is necessary to search for new drugs. In this context, there was an interest in studying palmatine, which is an isoquinolinic alkaloid, which has been used in traditional Chinese medicine for several years, presenting several pharmacological properties, including antifungal. The objective of this work was to evaluate the antifungal activity of palmatina against Candida spp. Resistant to azoles. The methodology used to verify the antifungal action was the broth microdilution technique. Flow cytometry tests were performed to elucidate the possible mechanisms of death involved. The anticancer action of palmatine was verified in biofilms formed and in formation in the three main Candida species (C. albicans, C. tropicalis, C. parapsilosis). Proteomic analysis was also used as a tool to understand the biochemical processes involved in the action of palmatine and the cytotoxicity test was also performed on murine fibroblasts. Palmatina demonstrated antifungal activity with MICs ranging from 32 to 128 μg / mL. It was found that palmatine reduced cell density, caused DNA damage, promoted mitochondrial depolarization, increased phosphatidylserine outgrowth, suggesting cell death by apoptosis. In biofilms formed, palmatine reduced the cellular viability of the biofilm in a concentration of 20x MIC (C. albicans) and 10x MIC (C. tropicalis and C. parapsilosis) by 50%. In biofilms in formation, the same percentage of inhibition was achieved in the MIC concentration (C. albicans) and 2x MIC (C. tropicalis and C. parapsilosis). Proteomic analysis of a strain of C. albicans exposed to palmatine demonstrated the overexpression of proteins related to energy production and synthesis of macromolecules. Palmatine did not demonstrate cytotoxicity when evaluated at the concentration of 100 μg / mL in murine fibroblast L929 cells. The antifungal action of palmatine in Candida spp. Resistant to planktonic and biofilm forming and forming biofilms, as well as being non-cytotoxic to animal cells, point to a promising new molecule or anti-plaque prototype.